2014
DOI: 10.1002/anie.201402125
|View full text |Cite
|
Sign up to set email alerts
|

A Bio‐Inspired Switch Based on Cobalt(II) Disulfide/Cobalt(III) Thiolate Interconversion

Abstract: Disulfide/thiolate interconversion supported by transition-metal ions is proposed to be implicated in fundamental biological processes, such as the transport of metal ions or the regulation of the production of reactive oxygen species. We report herein a mononuclear dithiolate Co(III) complex, [Co(III)LS(Cl)] (1; LS=sulfur containing ligand), that undergoes a clean, fast, quantitative and reversible Co(II) disulfide/Co(III) thiolate interconversion mediated by a chloride anion. The removal of Cl(-) from the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
(30 reference statements)
4
39
0
Order By: Relevance
“…We have previously reported that the cyclic voltammogram (CV) of Mn II 2 SH displays an irreversible anodic peak potential (E pa )a tÀ0.01 V, which was assigned to at wo-electron, metal-based oxidation. [8] The corresponding cathodic potential( E pc = À0.47 V) is consistentw ith af ast chemicalrearrangementand is attributed to the deprotonation of the thiol group after oxidation, which led to [Mn III 2 (LS) 2 ](PF 6 Àdisulfide/Mn III Àthiolate interconversion, which involves the coordination and release of the iodide anion, was analyzed and is reported, in comparison with the corresponding Co II 2 Àdisulfide/Co III Àthiolates ystem,i n the followings ections.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…We have previously reported that the cyclic voltammogram (CV) of Mn II 2 SH displays an irreversible anodic peak potential (E pa )a tÀ0.01 V, which was assigned to at wo-electron, metal-based oxidation. [8] The corresponding cathodic potential( E pc = À0.47 V) is consistentw ith af ast chemicalrearrangementand is attributed to the deprotonation of the thiol group after oxidation, which led to [Mn III 2 (LS) 2 ](PF 6 Àdisulfide/Mn III Àthiolate interconversion, which involves the coordination and release of the iodide anion, was analyzed and is reported, in comparison with the corresponding Co II 2 Àdisulfide/Co III Àthiolates ystem,i n the followings ections.…”
Section: Resultsmentioning
confidence: 54%
“…[7,9] This new complexi si sostructural to the previously described Co II -parent compound Co II 2 SS,w hich displays the same symmetry. [6] As in the case of complex Co II 2 SS,t he disulfide remains coordinated to the metal ions despite the fact that only aw eak interaction is expected between ad isulfide and d 5 Mn II ions. The {Mn 2 S 2 }c ore is quasi-planar;d eviation from the S1 Mn1 S1' Mn1' plane is < 0.059 , and the angle between the S1 Mn1 S1' and S1 Mn1' S1' planesi s8 .538.T he Mn sites are equivalent because of a C 2 symmetry axis that is or-Scheme1.Synthesis/electrosynthesis of the described manganese sulfur complexes.…”
Section: Structural Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The reaction of the dinuclear Co 2 SS 2 + + complex in the presence of two equivalents of Et 4 NCl leads to CoCl in good yield. [25] In this reaction, the coordination of one chloride anion on each Co II centeri nCo 2 SS 2 + + leads to the reduction of the disulfide bridge and the concomitanto xidation of the Co II ions. Following the same procedure, the addition of two equivalents of Et 4 From these two angles, the index of the degree of trigonality of ap entacoordinated geometry can be determined: t 5 = (bÀa)/60, in which a and b are the greatestt wo basal angles and a < b.F or ap erfectly tetragonal pyramidal geometry, t 5 is equal to zero, whereas it becomes equal to one for ap erfectly trigonal-bipyramidalg eometry.…”
Section: Synthesis and Structuresmentioning
confidence: 99%
“…In particu- [a] Data takenf rom Ref. [25]. www.chemeurj.org lar,t he energies of transitions (2) and (3) are noticeably more affected by the nature of the halide than that of (1).…”
Section: Electronicabsorption Propertiesmentioning
confidence: 99%